Clean Air and Cool Planet, Volume II : Integrated Air Quality Management and Greenhouse Gas Reduction for Almaty and Nur-Sultan - World Bank (Washington, DC, 2022)
The report synthesizes key findings and recommendations of a study carried out under the World Bank’s Advisory Services and Analytics Program, ‘Central Asia: Climate and Environment Program,’ which aims to strengthen the capacity of Central Asian countries to achieve sustainable and resilient economic growth. It builds on a previous World Bank report, which provided the first national-level approximation of primary sources of air pollution in Kazakhstan. This city-level study highlights how potential synergies between air quality improvement and greenhouse gas reduction measures can be enhanced in a cost-effective manner. To identify and maximize these synergies and assess the measures’ cost-effectiveness at the city level, the study developed two new extensions to the Greenhouse Gas and Air Pollution Interactions and Synergies (GAINS) model—GAINS-City and GAINS-Policy and applied them in Almaty and Nur-Sultan, two major cities in Kazakhstan, for the first time. The report delivers evidence of the main causes of premature deaths from air pollution in Almaty and Nur-Sultan and offers guidance on cost-effective solutions to prevent them while making the cities better prepared for a low-carbon future. It provides high-level roadmaps for the cities' integrated air quality management and climate change mitigation to maximize synergies and manage tradeoffs. It proposes sequencing of actions until 2030 to save lives from poor air quality while facilitating long-term phase out of fossil fuels. Moreover, the report analyzes the need for policy reforms to incentivize implementation of cost-effective integrated measures by private economic actors. The report recognizes that reprioritizing policy actions slightly to maximize climate benefits may require some additional air quality management actions to address the unacceptably high burden that exposure to PM2.5 currently places on public health.